2001
DOI: 10.3171/spi.2001.94.2.0185
|View full text |Cite
|
Sign up to set email alerts
|

Can airway complications following multilevel anterior cervical surgery be avoided?

Abstract: Object. The authors conducted a study to determine how to avoid emergency postoperative reintubation and its associated morbidity in patients who have undergone multilevel anterior—posterior cervical spine surgery. Methods. In a group effort between the departments of anesthesia and neurosurgery, a protocol was developed to avoid having to reintubate patients postoperatively. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 24 publications
(26 reference statements)
3
57
1
Order By: Relevance
“…In addition, the more life-threatening complication of postoperative airway problems may occur in up to 6% of patients. 4,9,11,29 Kepler et al 16 also found significantly increased dysphagia and soft-tissue shadowing on postoperative radiographs after 1-and 2-level ACDFs. The swelling decreased by 6 weeks but remained significant.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, the more life-threatening complication of postoperative airway problems may occur in up to 6% of patients. 4,9,11,29 Kepler et al 16 also found significantly increased dysphagia and soft-tissue shadowing on postoperative radiographs after 1-and 2-level ACDFs. The swelling decreased by 6 weeks but remained significant.…”
Section: Discussionmentioning
confidence: 94%
“…The severity and potential life-threatening nature of these complications from anterior cervical spinal surgery have prompted more thorough evaluations of their incidence and associated risk factors. 3,6,9,11,13,19,24,[27][28][29]33 The reported rates of dysphagia after anterior cervical surgery have varied widely, from 1% to 79%. 9 In a prospective study, Lee et al 19 found the prevalence of postoperative dysphagia at 1, 2, 6, 12, and 24 months to be 54%, 34%, 19%, 15%, and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All were present in the case reported here. Epstein et al also noted asthma, age > 65 year, obesity (> 100kgs) and severe postoperative neurological deficit (8). Prolonged and excessive deep tissue retraction can be a predisposing factor in the development of UAO.…”
Section: Stefanutto Tb Et Al Cervical Decompression and Unexpected Smentioning
confidence: 98%